2009
DOI: 10.2967/jnumed.108.056705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Morphology on Dosimetric Calculations for Internal Irradiation as Assessed by Comparisons of Monte Carlo Versus Conventional Methodologies

Abstract: Dosimetric calculations are performed with an increasing frequency before or after treatment in targeted radionuclide therapy, as well as for radiation protection purposes in diagnostic nuclear medicine. According to the MIRD committee formalism, the mean absorbed dose to a target is given by the product of the cumulated activity and a dose-conversion factor, known as the S factor. Standard S factors have been published for mathematic phantoms and for unit-density spheres. The accuracy of the results from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
6
36
0
1
Order By: Relevance
“…Because of the limitations of this model, alternative approaches to tumor dosimetry using dose-point kernel or Monte Carlobased methods have been used in some recent internal emitter therapy studies. 19,20 In the present study, we used SPECT/CT-imaging data coupled with the Dose-Planning Method (DPM) Monte Carlo algorithm 21 to carryout patientspecific estimation of the mean radiation-absorbed dose to tumor. The calculation also provided 3D dose distributions and results of the 3D dose measures, including dose response, were reported in a previous publication 3 and are not the focus of the present work.…”
Section: Tumor Dosimetrymentioning
confidence: 99%
“…Because of the limitations of this model, alternative approaches to tumor dosimetry using dose-point kernel or Monte Carlobased methods have been used in some recent internal emitter therapy studies. 19,20 In the present study, we used SPECT/CT-imaging data coupled with the Dose-Planning Method (DPM) Monte Carlo algorithm 21 to carryout patientspecific estimation of the mean radiation-absorbed dose to tumor. The calculation also provided 3D dose distributions and results of the 3D dose measures, including dose response, were reported in a previous publication 3 and are not the focus of the present work.…”
Section: Tumor Dosimetrymentioning
confidence: 99%
“…These models are generally formulated using either solutions of the transport equations [40,41], Monte Carlo calculations [39,[42][43], or convolutions of tabulated data from experimental sources such as thin foil [44] or PET/SPECT measurements [45,46]. Each of these methods have their advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Solving the transport equations, as is used here for instance, is a fast and robust method but without the previously mentioned mass attenuation coefficients and analytical solutions for the spherical geometry, requires significant numerical calculations [41]. Similarly, Monte Carlo methods have been very successfully used in dosimetry, but require substantial computational effort to generate sufficient data sets [42,43]. Fortunately codes such as FLUKA [47] and Geant4 [48] are becoming increasingly robust and sophisticated and are being adapted for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…16 The underestimation of tumor dose due to neglecting this contribution was found to be in the range 10%-20%, which is comparable to the results of the present study. In a more recent study, focusing mainly on normal organ dosimetry Divoli et al 17 reported on the differences between results obtained using patient-specific Monte Carlo methodology and results obtained using the reference S-values implemented in OLINDA. Individual patient's CT images (total of 9 patients) were used to define the normal organs, whereas published biodistribution data were used to assign cumulated activities.…”
Section: Comparison Of Patient Tumor Dose Assessmentsmentioning
confidence: 99%
“…Previous reports on such comparisons have either focused on organ dosimetry or were limited to simulated tumor geo metries. 16,17 The goal of the present study is to compare mean tumor absorbed dose estimates using the unit sphere model incorporated in OLINDA with dose estimates from previously reported Monte Carlo calculations for NHL patients. Unlike previous reports, the present study uses actual patient SPECT/CT imaging data and tumors of varying size, shape, and uptake relative to background for this comparison.…”
Section: Introductionmentioning
confidence: 99%